2021
DOI: 10.3390/recycling6020025
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Recovery from Wastewater: Bioavailability of P Bound to Calcareous Material for Maize (Zea Mays L.) Growth

Abstract: (1) Phosphorus (P) is an essential plant nutrient, and P deficiency negatively affects plant growth and development. Furthermore, P is a finite and nonrenewable resource, and there is an urgent need to recover P from some of the important waste streams in society. Newly engineered calcareous materials (sol–gel coated cat litter (CATSAN®)) can bind P from wastewater in decentralized treatment systems and potentially enable P recycling into agricultural production by direct addition of the P saturated material. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The sorption process constitutes a relatively simple and passive method to overcome P removal limitations in these systems, as when it is installed the material will bind P without much interference when compared to chemical dosing for P removal by precipitation or by harvest of plant biomass. The P saturated material could ideally be used directly as soil amendment and for slow release of P [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The sorption process constitutes a relatively simple and passive method to overcome P removal limitations in these systems, as when it is installed the material will bind P without much interference when compared to chemical dosing for P removal by precipitation or by harvest of plant biomass. The P saturated material could ideally be used directly as soil amendment and for slow release of P [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The first is the recovery of phosphorus from the liquid phase, which is only 50% -60%. No one has given an explanation for the reasons behind the low efficiency of recovering P from phosphogypsum or the fact that in actuality, regardless of the original phosphorus content, the residual phosphorus concentration always stays within a specific set range (Jensen et al, 2021). This study will mathematically calculate this range to obtain a specific set range as well as to explain the presence of residual phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…The external filter would polish effluent from the TWs by removing the excess P, but also allow a straightforward material exchange once the filter material has become P saturated, in comparison to exchanging the entire main bed of the TW. Another advantage of the external filter is its ability to make P more accessible for reuse and research has indeed already shown the potential use of P-enriched filter materials as a slow-release P fertilizer [16,17]. The recovery of P is important, as P is a limited and non-renewable resource [18,19], but also an essential plant nutrient with P deficiency negatively affecting plant growth [20].…”
Section: Introductionmentioning
confidence: 99%